Rendimiento y eficiencia agronómica de la fertilización magnésica en plátano (Musa AAB Simmonds) - Alcívar Matos, Frank Bruno (2022)
Magnesium is a key nutrient to enhance the yield of the plantain crop, even more so in soils with base imbalances, where deficiencies are recurrently manifested, which has a negative impact on yield. The aim of the research was to evaluate the yield and agronomic efficiency of magnesium fertilization in plantain. Three level of MgO (30, 60 and 90 kg ha-1) plus a treatment with omission of MgO were evaluated. A randomized complete block design was used, with four treatments, five replicates and 20 experimental units. The main variables recorded were fruit yield - FY (kg ha-1), agronomic efficiency of MgO - AE MgO (kg of fruit kg-1 of applied MgO) and net economic benefit - NEB (USD ha-1). The FY and AE MgO were significantly influenced (<0.05) by the treatments evaluated. The FY was increased by 4.91, 7.09 and 8.31%, over the MgO omission treatment, with the doses of 30, 60 and 90 kg of MgO ha-1, respectively. The AE MgO showed an inversely proportional behavior with the increase of the doses. The highest NEB was reached by the dose of 60 kg MgO ha-1, with 408 USD ha-1. From an equilibrium point, the adequate doses of MgO for the banana crop are between 30 and 45 kg of MgO ha-1, so it would be convenient in future studies to determine the optimal doses between these intervals.